(3GdaUhd GddDdDjI aj CUhd abg GdYJQI GdfHhjIs - (3EHQGgje Hf eMeO Hf GdhRjQ,J (B914 (3g` s
(3ChdgG (B:s
(3GdMeO dgd hHYO agPg fNH eUWaGI ef CbhGd CFeJfG s
(3BNQgG (B:s
(3hbO jhSY HYV YdeGFfG hZjQge ai YOgG hMUgQG eJYSQ , aJQGLY HSGFWgG hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B65s
Keywords: (3Gdabg GdESdGejs